2017
DOI: 10.17116/oftalma201713324-9
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront aberrations and accommodation in myopes and hyperopes

Abstract: Myopia has been shown to be associated with reduced accommodation parameters as well as stronger HOA and pseudoaccommodation. Wavefront and accommodation parameters interrelations differ in myopic and hyperopic eyes. The nuances revealed should be taken into account when developing correction methods that purposefully influence refractogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(14 reference statements)
0
6
0
2
Order By: Relevance
“…This study includes all type of spherocylindrical errors. 4,5 While there is significant difference between hypermetropes and normal individuals as p value is 0.001. Our results that there is significant difference between range of accommodation in all refractive errors (myopes, hypermetropes) and normal population are not new but to the best of our information this is only studies which showed the comparison between these two procedures.…”
Section: Comparison Of Association Of Range Of Accommodation Between Myopes Hypermetropes and Normal Individualsmentioning
confidence: 94%
See 1 more Smart Citation
“…This study includes all type of spherocylindrical errors. 4,5 While there is significant difference between hypermetropes and normal individuals as p value is 0.001. Our results that there is significant difference between range of accommodation in all refractive errors (myopes, hypermetropes) and normal population are not new but to the best of our information this is only studies which showed the comparison between these two procedures.…”
Section: Comparison Of Association Of Range Of Accommodation Between Myopes Hypermetropes and Normal Individualsmentioning
confidence: 94%
“…This reflective mechanisms initiated by signals that activate the ciliary muscle, changing the shape of the crystalline lens and thus the power of the eye. 4,5 These signals should include the needed focus direction whether positive or negative. 6,7 The human eye has a maximum capacity of accommodation, known as accommodative amplitude (AA), which depends mainly on age.…”
Section: Introductionmentioning
confidence: 99%
“…Аккомодационный ответ. Низкая чувствительность аккомодации и ответ на расфокусирование изображения в фовеа может являться самостоятельным предиктором миопии [31][32][33][34][35][36][37]. Снижение аккомодационного ответа вблизи и длительная зрительная работа на коротких дистанциях с низким наклоном головы являются прогностически значимыми факторами для оценки вероятности развития миопии [18,28,38].…”
Section: обзоры литературыunclassified
“…Сферическая аберрация. Известно, что сферическая аберрация (СА) оказывает физиологическое влияние на развитие глаза [33][34][35][36][37]. Положительная СА ингибирует его рост, снижая тенденцию к развитию близорукости [39][40][41].…”
Section: обзоры литературыunclassified
“…Hyperopia, accounting for a relatively small proportion of surgical cases in Asian countries, 1 is a clinical challenge for optometrists because of high accommodation. 2 The wavefront aberrometer has been widely used to measure ocular aberrations, including lower-order spherical error and astigmatism. 3 Thus wavefront supported custom ablation (WASCA) provides an alternative for refraction testing and for the assessment of the accuracy of refractive surgery.…”
Section: Introductionmentioning
confidence: 99%